The influence of legislators' endorsements in party leadership elections. Issue 4 (3rd December 2018) - Hanretty, Chris
Abstract In the 2010 election for the post of leader of the British Labour party, almost all members of parliament endorsed one of five leadership candidates. I investigate the effect of these endorsements on the votes cast for candidates in each Westminster constituency. I find that an MP's endorsement caused an average increase of 7.5 percentage points in the vote share of the endorsed candidate in that MP's constituency.